1980
DOI: 10.1002/1097-0142(19801001)46:7<1641::aid-cncr2820460725>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy, aggressiveness, and recurrence in giant cell tumor of bone

Abstract: Eighty-six cases of giant cell bone tumor were reviewed with particular attention to frank sarcomatous changes, abnormal mitoses, permeation of vascular channels, and the number of mitoses per square millimeter, and the results were analyzed in relation to malignancy, aggressiveness, and recurrence. There were 4 cases of malignant (Grade III) tumor (about 5%) showing frank sarcomatous changes. Eight (9%) were considered cases of borderline (Grade II+) tumor, without frank sarcomatous changes but showing abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
2
3

Year Published

1983
1983
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(84 citation statements)
references
References 12 publications
3
76
2
3
Order By: Relevance
“…Authors have suggested several etiologies and mechanisms of metastasis in GCT including transformation from a self-limited benign course and true arterial metastasis [4,8,15,16,18]. Postulated mechanisms could be either embolism or active ''biologic predeterminism'' of the giant cells to invade the interstitium, destroy vessel walls, and intravasate by means of enzymes with subsequent lodgment and growth in target organs [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have suggested several etiologies and mechanisms of metastasis in GCT including transformation from a self-limited benign course and true arterial metastasis [4,8,15,16,18]. Postulated mechanisms could be either embolism or active ''biologic predeterminism'' of the giant cells to invade the interstitium, destroy vessel walls, and intravasate by means of enzymes with subsequent lodgment and growth in target organs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Postulated mechanisms could be either embolism or active ''biologic predeterminism'' of the giant cells to invade the interstitium, destroy vessel walls, and intravasate by means of enzymes with subsequent lodgment and growth in target organs [4]. There also is debate regarding whether surgical manipulation promotes pulmonary metastasis [4,8,15,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Jaffe et al [18], Dahlin et al [8], and Huvös [17] classified GCT into 3 grades by its histological appearance, but the clinical and prognostic value of this grading has been disputed because these criteria are, in part, subject to personal bias [9,26].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the usual lightmicroscopic features associated with aggressive clinical behavior in most neoplasms, including necrosis, mitotic activity and even vascular invasion, do not predict outcome in giant-cell tumor. 1,8 The discrepancy between histopathology and clinical course may stem from the heterogeneous population of cells that constitute giant-cell tumor. More specifically, culture experiments suggest that the neoplastic cells of giant-cell tumor represent only a small subset of a mixed population of cells that include monocyte-macrophages, osteoclast-like giant cells and others.…”
mentioning
confidence: 99%
“…Some authors have suggested that radiologic grade simply predicts the likelihood of adequate treatment, and it is the latter that influences clinical behavior. 8 Giant-cell tumor is typically treated with intralesional curettage, burring and packing with cement or bone graft. More aggressive treatment protocols involve resection so as to achieve wider margins than are customarily accomplished with intralesional curettage procedures.…”
mentioning
confidence: 99%